Strategi dan Motivasi Siswa SDN Pacarkembang 1 Menembus OSN Matematika Tingkat Kota - Zahroh, Fitratuz; Farih, Nadhyva Maulida (ARZUSIN, 2025)
This study is motivated by the low quality of education in Indonesia, as reflected in the 2022 PISA survey results, particularly in Mathematics, which highlight that mastering numeracy competencies remains a major challenge. This issue is of particular concern in the context of high achieving students. The purpose of this study is to analyze the learning strategies and self motivation of students who have excelled in the National Science Olympiad (Olimpiade Sains Nasional or OSN) in Mathematics at the city level. A qualitative approach was used with a case study design, and the research subject was a sixth grade student at SDN Pacarkembang 1/192 Surabaya who had achieved success in the OSN. Data collection techniques included in depth interviews, participatory observation, and documentation, which were thematically analyzed to explore learning patterns and success supporting factors. The findings reveal that the student applied structured learning strategies, such as the Pomodoro technique, drill and practice, and intensive pattern recognition of questions. The student’s learning motivation was combinative, consisting of intrinsic motivation such as a strong desire to master Mathematics, and extrinsic motivation including the desire for recognition and certificates. External factors such as parental and teacher support, as well as the use of technology and digital learning resources, were also found to be significant in supporting the student’s success. The main conclusion of this study is that success in academic competitions like OSN is determined not only by cognitive ability but also by a combination of effective learning strategies, strong self motivation, and a holistically supportive learning environment. The implications of this study include contributions to the literature on achievement oriented Mathematics learning, and practical recommendations for teachers and parents to create conducive learning environments that support the development of numeracy and students’ academic potential. This study also opens opportunities for further research on educational interventions to optimally nurture gifted students.